Association of Uric Acid and Atherogenic Index Of Plasma in Diabetes Mellitus (Bangladesh Journal of Medical Biochemistry, 2023)
Diabetes mellitus (DM) is a chronic disease characterized by insulin deficiency or peripheral resistance resulting in hyperglycemia. Diabetic patients have increased rates of coronary heart disease, cerebrovascular disease and peripheral vascular disease, and are two to three times more likely to develop cardiovascular disease (CVD). Serum uric acid (SUA) has been known to be associated with cardiovascular diseases. "Atherogenic index of plasma" (AIP) is considered to be a very sensitive predictor of future cardiovascular events. The study was done to evaluate the association of serum uric acid and atherogenic index of plasma in diabetic patients. A total of 315 diabetic patients were selected as study subjects based on predefined enrollment criteria. The patients were separated into groups according to their serum uric acid levels. Serum uric acid levels under 6 mg/dL were considered as normal. AIP was calculated as the logarithmically transformed ratio of triglyceride to high density lipoprotein cholesterol. The study found that AIP levels were significantly high in high SUA group compared to normal SUA group. The study showed a positive significant correlation between AIP and SUA (r=0.347, P